Update Informasi Jumlah Terpapar Covid-19 Lewat Sosial Media Sebagai Informasi Warga Desa Sukajadi, Kabupaten Ciamis Untuk Siap Siaga Covid-19 - Krisna Mahardika; Muh. Sulaiman Dadiono; Rudy Wijaya; Kasprijo Kasprijo (Abdi Jaya : Jurnal Pengabdian Indonesia, 2024)
Covid-19 which emerged in early 2020 has had a major impact on Indonesian society, especially in economic, social, and health aspects. Throughout 2020 to 2021, the number of Covid-19 cases in Indonesia increased sharply, one of which was due to low public awareness of prevention efforts. As a solution, the latest information related to Covid-19 was published through posters distributed on social media such as WhatsApp and Instagram. This step aims to be a rapid prevention effort, especially in Sukajadi Village, Ciamis Regency. The purpose of this publication activity is to increase public awareness of Covid-19 prevention while providing information on the latest developments in Covid-19 cases. The methods used in this activity include *Participatory Rural Appraisal* to actively involve community participation, as well as surveys to understand the information needs of the community. The results of this activity show an increase in understanding and awareness of Sukajadi Village residents regarding the importance of accurate information related to Covid-19.